PERAN GENDER DALAM RUMAHTANGGA MASYARAKAT PULAU KECIL (STUDI KASUS KECAMATAN TELUK AMBON BAGUALA KOTA AMBON) - Junianita Fridianova Sopamena (JURNAL AGRIBISNIS TERPADU, 2019)
Role division in households between man and woman has been the cultural legacy of the community. This division put man as family head and women as housewife. Roles of men and women are beginning to shift recently, and this phenomenon is identified as gender role displacement. Research is aimed to analyze gender role in households of small island community. This research is using qualitative descriptive approach that utilizes key informant as the main source of information, who then will be set into harmony with other informants. Waeheru Village and Passo Village are selected as research location. The former provides 17 informants while the latter gives 67 informants. Total informant is 84 persons. Result of research shows that gender role displacement is really occuring in the households of small island community. Woman helps the husband to serve household necessities through various economic activities. In general, woman in small island does many economic activities relating with crop planting, gardening, animal husbandry, and fishery. The variety of activity that woman should do is indicating the variety of gender role that woman must play. Woman activities indeed have great contribution to the fulfillment of household necessities in small island community.